PALINOLOGIA ESTRATIGRAFICA DEL JURASICO DE LA SIERRA DE CHACAI CO Y ADYACENCIAS (CUENCA NEUQUINA, REPUBLICA ARGENTINA). II. DESCRIPCION DE LOS PALINOMORFOS DEL JURASICO INFERIOR Y AALENIANO (FORMACIONES SIERRA CHACAl CO Y LOS MOLLES) (Ameghiniana, 2013)
"In this Part II, systematic descriptions and/or microphotographs of 53 species of palynomorphs from the Lower Jurassic and Aalenian (Sierra Chacai-Co Formation and Los Molles Formation) from the southern border of the Neuquén Basin are presented. They belong to the following genera: Deltoidospora, Todisporites, Dictyophyllidites, Biretisporites, Concauisporites, Auritulinasporites, Osmundacidites, Verrucosisporites, Rugulatisporites, Cadargasporites, Ceratosporites, Lycopodiumsporites, Ischyosporites, Gleicheniidites, Neoesisporites (trilete miospores); Aratrisporites (?), Peromonolites, Punctatosporites (monolete miospores); Callialasporites, V itreisporites, Alisporites, Podocarpidites (saccate pollen); Cycadopites, Monosulcites, Cerebropollenites, Equisetosporites (colpate pollen ) ; Perinopollenites, Classopollis (porate pollen}; lnaperturopollenites, Araucariacites (alete pollen). The acritarchs are represented by species of the genera Baltisphaeridium, Micrhystridium, Campenia, Lancettopsis, Pterospermopsis, Pleurozonaria. The microfloras of the Cura Niyeu Formation and Lajas Formation will follow in Part III. New taxon: Campenia austroamericana."